The potential roles of different metacaspases in maize defense response - Ma, Shijun (Plant Signal Behav, 2021)
Metacaspases (MCs), a class of cysteine-dependent proteases, act as important regulators in plant defense response. In maize genome, there are 11 ZmMCs which have been categorized into two types (type I and II) based on their structural differences. In this study, we investigated the different transcript patterns of 11 ZmMCs in maize defense response mediated by the nucleotide-binding, leucine-rich-repeat protein Rp1-D21. We further predicted that many cis-elements responsive to salicylic acid (SA), methyl jasmonate (MeJA), abscisic acid (ABA) and auxin were identified in the promoter regions of ZmMCs, and several different transcription factors were predicted to bind to their promoters. We analyzed the localization of ZmMCs with previously identified quantitative trait loci (QTLs) in maize disease resistance, and found that all other ZmMCs, except for ZmMC6-8, are co-located with at least one QTL associated with disease resistance to southern leaf blight, northern leaf blight, gray leaf spot or Fusarium ear rot. Based on previous RNA-seq analysis, different ZmMCs display different transcript levels in response to Cochliobolous heterostrophus and Fusarium verticillioides. All the results imply that the members of ZmMCs might have differential functions to different maize diseases. This study lays the basis for further investigating the roles of ZmMCs in maize disease resistance.